Crises and the Roman Empire : proceedings of the Seventh Workshop of the international network Impact of Empire, Nijmegen, June 20-24, 2006 - Hekster, Olivier.; Kleijn, Gerda de.; Slootjes, Daniëlle. (Impact of Empire, 2007)
This volume presents the proceedings of the seventh workshop of the international thematic network 'Impact of Empire', which concentrates on the history of the Roman Empire and brings together ancient historians, archaeologists, classicists and specialists on Roman law from some 30 European and North American universities. The seventh volume focuses on the impact that crises had on the development and functioning of the Roman Empire from the Republic to Late Imperial times. The following themes are treated: the role of crises in the empire as a whole; the relationship between crises and the Roman economy; modes in which crises influenced the presentation of emperors, and the impact of crises on and reception in (legal) writings.